Influencing Factors of Online Learning Courses Satisfaction in Art Major: A Case Study of Chongqing, China - Yue, Wu (Scholar: Human Sciences, 2025)
Purpose: This study employs a mixed-methods approach to investigate online learning satisfaction of students in art education. It determines relationship between self-efficacy, content quality, interactivity, delivery method, social presence, and satisfaction with online learning course. Research design, data, and methodology: Qualitative methods include observations, interviews, and surveys, capturing insights into students’ experiences and challenges. The target population is students, majoring in art at the School of Journalism and Communication, Sichuan International Studies University. Index of Item-Objective Congruence and pilot test were implemented to prove validity and reliability of the research items. The quantitative phase involves administering structured questionnaires to 80 students and analyzing data using SPSS. The strategic plan involves 30 students. Results: Integrating qualitative and quantitative findings, the study offers a comprehensive understanding of satisfaction in online art education. The paired-sample T-test analysis results for six variables related to student satisfaction, comparing the phases before and after implementing a strategic plan, has been found significant mean different. Conclusions: The research contributes to the discourse on online learning satisfaction, offering implications for designing effective online art education programs.